A note on warped product submanifolds of cosymplectic manifolds - Uddin, S.; Khan, V.A.; Khan, K.A. (Faculty of Science and Mathematics - University of Nis, 2010)
In this paper, we study warped product anti-slant submanifolds of cosymplectic manifolds. It is shown that the cosymplectic manifold do not admit non trivial warped product submanifolds in the form N(perpendicular to) x (f)N(theta) and then we obtain some results for the existence of warped products of the type N(theta) x (f)N(perpendicular to), where N(perpendicular to) and N(theta) are anti-invariant and proper slant submanifolds of a cosymplectic manifold (M) over bar, respectively.